2005
DOI: 10.1038/nsmb921
|View full text |Cite
|
Sign up to set email alerts
|

Hemifusion in SNARE-mediated membrane fusion

Abstract: SNAREs are essential for intracellular membrane fusion. Using EPR, we determined the structure of the transmembrane domain (TMD) of the vesicle (v)-SNARE Snc2p involved in trafficking in yeast. Structural features of the TMD were used to design a v-SNARE mutant in which about half of the TMD was deleted. Liposomes containing this mutant induced outer leaflet mixing but not inner leaflet mixing when incubated with liposomes containing target membrane (t)-SNAREs. Hemifusion was also detected with wild-type SNARE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
235
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(253 citation statements)
references
References 35 publications
15
235
3
Order By: Relevance
“…Hemifusion can be induced in a minimal SNARE-driven liposome fusion system by low levels of wild-type SNARE proteins or by mutant SNARE proteins that have partial TMDs that only span the outer bilayer leaflet (6). A hemifusion intermediate was also detected at the single-liposome level by monitoring FRET between membrane-bound fluorophores in single fusion events between pairs of SNARE-reconstituted liposomes (7), and in flipped SNARE-mediated cell-cell fusion (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemifusion can be induced in a minimal SNARE-driven liposome fusion system by low levels of wild-type SNARE proteins or by mutant SNARE proteins that have partial TMDs that only span the outer bilayer leaflet (6). A hemifusion intermediate was also detected at the single-liposome level by monitoring FRET between membrane-bound fluorophores in single fusion events between pairs of SNARE-reconstituted liposomes (7), and in flipped SNARE-mediated cell-cell fusion (8).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that membrane fusion may require a lipidic ''hemifusion'' intermediate, where the closely apposed membrane leaflets are fused and mix, whereas the distal leaflets and aqueous compartments remain distinct. Hemifusion has been directly observed with influenza HA (3)(4)(5), either wild-type or with a GPI-anchor in place of its transmembrane domain (TMD), in a minimal SNARE-driven liposome fusion system (6, 7) with low levels of wild-type SNARE proteins or with mutant SNARE proteins with partial TMDs that span only one bilayer leaflet (6). Hemifusion was also observed in cell-cell fusion mediated by GPI-anchored SNARE proteins expressed on the outer surface of the plasma membrane (8), suggesting that all SNARE-dependent fusion might proceed by means of hemifusion.…”
mentioning
confidence: 99%
“…Recent studies have suggested that this process proceeds through a hemifused state in which the outer membrane leaflets fuse first, followed by fusion of the inner membrane leaflets (10)(11)(12)(13). Formation of the hemifused state is characterized by significant physical constraints, because the outer leaflet needs to bend in a tight negative curve to preserve membrane integrity.…”
Section: Snap23 ͉ Syntaxin 4 ͉ Vamp2mentioning
confidence: 99%
“…Closely related to this is the work suggesting that fusion proceeds through a hemifusion intermediate [26,27]. This argues for a fusion pore composed of lipid rather than of protein as proposed by Han et al [21,22].…”
Section: Fusion Pores and Molecular Mechanisms Of Exocytosismentioning
confidence: 57%